Strength profile in young male athletes from different sports - Busko, K.; Gajewski, J.; Mazur-Rózycka, J.; Michalski, R.; Lach, P. (Biomedical Human Kinetics, 2013)
Study aim: The aim of the present study was to determine a strength profile which characterizes young male athletes from different sports and to use the method of allometry to synthetically evaluate the muscular strength with respect to body mass.